Natalia Gryzunova THE INFLUENCE OF MISSELLING ON FORMING TECHNOLOGY PORTFOLIO INVESTMENT - N. V. Gryzunova (Вестник Северо-Кавказского федерального университета)
For more than a decade, Russian companies have been operating under a lack of investment. The main source of investment is traditionally own funds, which reduces the business activity and competitiveness of the company. The reason for the high share of own capital in the structure of liabilities - long-term Bank misselling. Of course, the companies informed the Supervisory authorities about this situation, but without success. The lack of measures of the regulator economic policy caused pessimism in the debt market and a reduction in the volume of claims against financial institutions. International practice, however, provides precedents of successful response to misselling and the creation of protective mechanisms.The article considers the transformation of the portfolio approach and offers recommendations for overcoming the credit deficit without using misseling for industrial companies and liquidity risk for banks.